Acute effects of dry land resistance training sessions on the subsequent sprint swimming training before and after COVID-19 pandemic - Toubekis, A.; Arsoniadis, G.; Botonis, P.; Bogdanis, G.; Terzis, G. (XIVth International Symposium on Biomechanics and Medicine in Swimming Proceedings, 2023)
The aim of the study was to examine the acute effect of dry land maximum strength (MS) or strength endurance (SE) training on the subsequent sprint swimming training, before and after a period of swimming training cessation due to COVID-19 pandemic.